2024
DOI: 10.1101/2024.01.11.24301142
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiology and burden of respiratory syncytial virus in Italian adults: A systematic review and meta-analysis

Alexander Domnich,
Giovanna Elisa Calabrò

Abstract: Objective Respiratory syncytial virus (RSV) is a common respiratory pathogen not only in children, but also in adults. Country-specific data on the epidemiology and burden of disease are essential for policy decisions. In view of a recent authorization of adult RSV vaccines, we aimed to comprehensively collect and assess evidence on the epidemiology and burden of RSV in Italian adults. Methods A systematic literature review was conducted according to the available guidelines. Random-effects proportional meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
0
0
Order By: Relevance
“…Every year, in Europe, 1 in 20 elderly people contracts RSV, and the infection accounts for approximately 160,000 hospitalizations, 95% of which occur in people aged 65 and older [9,10]. RSV imposes a quantifiable burden on adults in Italy, particularly among older individuals and those with underlying comorbidities [11,12]. A recent meta-analysis suggests that approximately 4.4% of respiratory samples from older adults tested positive for RSV infection [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Every year, in Europe, 1 in 20 elderly people contracts RSV, and the infection accounts for approximately 160,000 hospitalizations, 95% of which occur in people aged 65 and older [9,10]. RSV imposes a quantifiable burden on adults in Italy, particularly among older individuals and those with underlying comorbidities [11,12]. A recent meta-analysis suggests that approximately 4.4% of respiratory samples from older adults tested positive for RSV infection [12].…”
Section: Introductionmentioning
confidence: 99%
“…RSV imposes a quantifiable burden on adults in Italy, particularly among older individuals and those with underlying comorbidities [11,12]. A recent meta-analysis suggests that approximately 4.4% of respiratory samples from older adults tested positive for RSV infection [12]. Moreover, an analysis on the severity of RSV infection in older patients observed that LRTD was present in 29.5% of hospitalized patients aged 65 and above, non-invasive ventilation was implemented in 16.3%, and in-hospital death occurred in 12.1% [13].…”
Section: Introductionmentioning
confidence: 99%